Tenosinovitis por Mycobacterium chelonae : A propósito de un caso. - BERROCAL KASAY, Alfredo (2013)
We report a patient with a diagnosis of synovial tenosynovitis who developed septic tenosinovitis with cold abscess on right hand, after a local punction. Mycobacterium chelonae a fast-growing mycobacteria, was isolated. We discuss aspects related to differential diagnosis, epidemiology, risk factors. diagnostic procedures and issues related to treatment of this nosocomial infection.